Electrochemical Performance of Ti-Based Commercial Biomaterials - E. Porcayo-Palafox; S. I. Carrera-Chavez; S. R. Casolco; J. Porcayo-Calderon; V. M. Salinas-Bravo (Advances in Materials Science and Engineering)
In order to determine the electrochemical behavior against the corrosion of different commercial biomaterials, in this study the results of the evaluation of different titanium implants are reported. The commercial implants evaluated were purchased randomly with different suppliers. The different biomaterials were subjected to studies of potentiodynamic polarization curves, open circuit potential measurements, linear polarization resistance measurements, and electrochemical impedance spectroscopy measurements in a 0.9% NaCl solution. The results showed that the chemical composition of the biomaterials corresponds to commercially pure Ti or to the alloy Ti6Al4V. In addition, although all the biomaterials showed a high resistance to corrosion, notable differences were observed in their performance. These differences were associated with the thermomechanical processes during the manufacture of the biomaterial, which affected its microstructure.